Range extension of Pseudotorinia phorcysi (Gastropoda: Architectonicidae) from the SW Atlantic, with remarks on its ontogeny - Cavallari, Daniel C.; Salvador, Rodrigo B. (Zootaxa, 2016)
Architectonicidae is a diverse family of heterobranch sea snails comprising over 11 genera and 140 extant species distributed worldwide (Bieler & Petit, 2005). They live in shallow to deep water, and have turbinate to discoidal shells, with a typically wide umbilicus and a downward-pointing (heterostrophic) protoconch (Healy, 1998). Pseudotorinia phorcysi Cavallari, Salvador & Simone, 2013 is a deep-water species known only from its type locality in the SW Atlantic, off Cabo Frio, Rio de Janeiro state, Brazil (23°41’S 42°06’W, 430–450 m depth). Its original description was based on a single eroded juvenile specimen collected by the French-Brazilian expedition “Marion Dufresne” MD55 in the late 1980s (Cavallari et al., 2014).